Performance evaluation of time-based black hole attack detection in mobile ad hoc networks - Raja Mahmood, Raja Azlina; Hussin, Masnida; Manshor, Noridayu; Khan, A. I. (IEEE (IEEE Xplore), 2014)
Efficient and quick attack detection is critical in any networks, especially if the attack is harmful and can bring down the whole network within a short period of time. A black hole or packet drop attack is one example of a harmful attack in mobile ad hoc networks. In this study, we implement a series of time-based black hole attack detection of different time intervals and compare the results. We study the performances of the networks, the packet delivery ratio percentage, with detection interval time of 900, 450 and 300 seconds with a total of 900 seconds of simulation time. The results suggest that appropriate time interval is critical in providing reliable detection results in timely manner. In general, the 450 seconds detection interval time has provided more reliable results, with lower false positive percentage in comparison to those of the 300 seconds detection interval time. The best explanation to the high false positive rate in the shorter detection interval time is due to the insufficient time given to the packets to arrive to the destinations during the detection process. Meanwhile, implementing the attack detection only after 900 seconds may be considered too late and thus, may have a devastating impact to the networks.